2020
DOI: 10.1021/acs.macromol.0c01969
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Pair Radical Polymerization “On-Water”

Abstract: An unprecedented radical polymerization of various (meth)­acrylates, diethyl acrylamide, and 4-vinylpyridine initiated by Lewis pair (LP) catalysts, specifically PPh3/Cu­(OTf)2 or PPh3/Sn­(OTf)2, is reported herein. The reaction occurred at the interface between monomer and water phases, namely, “on-water”, at room temperature. The polymerization of (meth)­acrylates “on-water” was significantly more efficient than the reaction in organic solvents or in bulk. It was determined that the propagation occurs via a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The metal enolates in the monomer phase were not decomposed even in the presence of water, but they are reluctant to undergo anionic Michael addition, probably because of the protic nature of water and/or ligand exchange during polymerization. Activation of the monomer carbonyl groups on-water on the surface probably facilitates the LPRP, as previously proposed …”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…The metal enolates in the monomer phase were not decomposed even in the presence of water, but they are reluctant to undergo anionic Michael addition, probably because of the protic nature of water and/or ligand exchange during polymerization. Activation of the monomer carbonyl groups on-water on the surface probably facilitates the LPRP, as previously proposed …”
Section: Resultssupporting
confidence: 64%
“…The terminal structure and effects of various inhibitors were then analyzed for the polymerization of DEAA using various LAs with PPh 3 . The LAs, including Fe­(OTf) 3 , Cu­(OTf) 2 , In­(OTf) 3 , Ga­(OTf) 3 , Zn­(OTf) 2 , and Sn­(OTf) 2 , facilitated the LPRP on-water (see entries 1–4, Table ), whereas the LPAP in THF proceeded using Sc­(OTf) 3 , Y­(OTf) 3 , Zn­(OTf) 2 , and Sn­(OTf) 2 (entries 5, 6, 8, and 9 in Table ). Interestingly, the propagation mechanism depends on the solvent used, Zn­(OTf) 2 and Sn­(OTf) 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, it has been shown that organic reactions are significantly accelerated “on water”, that is, in heterogeneous medium with no solvation of the reaction components. [2] Hence, the observed reaction rates of Aldol reactions, [3] cycloaddition reactions, [4] multicomponent reactions, [5] polymerization reactions, [6] and even metal–organic reactions [1] are larger in heterogeneous aqueous medium as compared with the ones obtained in homogeneous solutions in organic solvents. The mechanistic origin of the apparently general phenomenon is still not fully understood and presently debated,[ 1 , 2a ] and it certainly depends on the respective specific interactions of the substrates with the surrounding medium.…”
Section: Introductionmentioning
confidence: 99%